CHEMICAL COMPOSITION AND EFFECTS THE DIETARY CORN BY-PRODUCTS ON BROILER PERFORMANCE - GEORGETA CIURESCU (Scientific Papers Animal Science and Biotechnologies, 2023)
The paper presents a study conducted in INCDBNA –BALOTEŞTI on 840 Ross- 308 broilers from hatching to 42 days. The broilers were assigned to 3 groups (control – C, and two experimental – GLU and GERM), with 280 broilers per group (3 groups × 2 replicates × 140 broilers). Three compound feeds formulations were used, one control and two experimental. The control diet was based on corn, soybean meal, full fat soy and fish meal; in the experimental groups the fish meal was replaced by corn gluten (GLU); in the other experimental group the full fat soy was replaced by corn germs (GERM). All compound feeds formulations were isoprotein, isocaloric and contained equal levels of total and digestible sulphur amino acids, lysine, calcium and available phosphorus, in agreement with the feeding requirements recommended for the intensive rearing of these performing hybrids. The broilers were phased feed with diets according to their age: start (0 – 14 days), growerdeveloper (15 – 28 days) and finisher (29 – 42 days). The monitored productive parameters were: average daily feed intake (g); body weight evolution by growth stage (g); feed conversion ratio (g feed/g gain); stock liveability (%); slaughtering yield and proportion of carcass parts (%), economic efficiency (%).